Trust in E-Retailing: Myth or Reality (KASBIT Business Journal, 2020)
E-retailing has set up its roots in all those areas where products and services are being exchanged either to a full extent or partially. The same amount of people is using it extensively in almost all aspects of life. There is a discrepancy in the trust in this type of buying and selling in the marketplace. So, this study was carried out to investigate the low levels of trust and low customer buying intention. The study highlighted t the factors that affect customer buying intention. Customer satisfaction being the direct and major source of influence on customer buying intention, it was also learned that the other three factors also have a significant impact on buying intention indirectly, as these factors agitate the customer satisfaction variable. These factors are service quality, reliability, and empathy. As assumed in the hypotheses, the results showed that the independent variables, service quality, reliability, empathy, and customer satisfaction have a profound effect on the dependent variable, that is, customer buying intention. The primary data was gathered through a questionnaire containing twenty-one closed-ended questions. The responses ranging from 1-5 on the Likert scale. The reliability test was run to check whether the data is unique and practical or not. Finally, Amos was run to check the dependency of the variables amongst each other.
Keywords: Customer satisfaction; service quality; reliability; empathy; e-service/ e-commerce